Technical bioanalytical considerations for detection and quantification of cytokines in ELISA assays. (March 2022) - Borges, Leandro; Dermargos, Alexandre; Hatanaka, Elaine
Highlights: The post-analytical phase is crucial to the reliability of the ELISA assay. Analytical noise and limit of detection/quantitation influence the sensitivity of immunoassays. Reverse pipetting and the spike-and-recovery test can reduce inter-assay variance. The linearity-of-dilution experiment can prevent the prozone (or hook) effect. Abstract: Enzyme-linked Immunosorbent Assays (ELISAs) techniques are widely known for the robust signal amplification with high sensitivity and specificity for the quantitation of antibodies and antigens in complex biological fluids. However, strict caution in the pre-analytical, analytical, and post-analytical phases is crucial to warrant an immunoassay quality. Since analytical errors are commonly seen in papers, this study aimed to discuss the main principles and guidelines to guarantee the specificity and sensitivity in the post-analytical phase of the ELISA method. Briefly, we highlighted the relevance of the analytical noise, as well as the limit of detection and quantitation, in the sensitivity of an immunoassay. Moreover, strategies involving the use of reverse pipetting and the spike-and-recovery test can decrease the inter-assay variance, while the linearity-of-dilution assay may protect against the prozone (or hook) effect. Addressed to researchers from different fields, we offer recommendations to limit variability and increase the usefulness of the ELISA assay in a practical way that will assist scientists to prevent future analytical errors.